The A CYCLO CONVERTER BASED INDUCTION MOTOR SPEED CONTROL (International Journal of Engineering Management Science, 2022)
The speed of the motor can be varied in two ways, one is by changing the number of poles and the second method is by changing the frequency. The speed control through the first method is uneconomical and the number of poles can’t be varied under running conditions and the size of the machine also becomes bulky. These problems can be overcome by the second method. In this method, the frequency can be varied under running conditions also and there is no change in the size of the motor. In this method, the frequency changing device is Cyclo-converter. A Cyclo-converter is a power electronic device used to convert constant voltage constant Frequency AC power to adjustable voltage adjustable frequency AC power without a DC link. In among all the methods this method is simple, reliable and economical. The various speed of induction motor is obtained by varying the supply frequency by using Cycloconverter. In the modern era, Power Electronic and motion control has emerged as a very important technology in the industrial automation. In the industrial process, most of the drives are constant torque type and need to drive such loads at different speeds, because of which generation of supply with variable frequency become essential. Single phase cycloconverters are used for AC-AC power conversion particular for speed control of AC drives. To avoid the voltage spikes that appear during the dead time, safe commutation strategy is employed. In this project we convert the single phase uncontrolled to single phase controlled output using cycloconverter and this is fed to a scott transformer to obtain three phase controlled output and these are going to be analyzed by MATLAB Simulink.